2012
DOI: 10.1083/jcb.201111042
|View full text |Cite
|
Sign up to set email alerts
|

A flagellar A-kinase anchoring protein with two amphipathic helices forms a structural scaffold in the radial spoke complex

Abstract: Amphipathic helices in the A-kinase anchoring protein RSP3 bind to spoke proteins involved in the assembly and modulation of the flagellar radial spoke complex, expanding the repertoire of these versatile helical protein motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 67 publications
8
34
0
Order By: Relevance
“…In agreement with the previous studies (Diener et al, 1993;Patel-King et al, 2004;Sivadas et al, 2012), RSP3 appears to be localized all the way from the RS head to the root of the RS stalk, and one spoke contains at least two copies of RSP3 (Figs. 2 and S1; Wirschell et al, 2008;Diener et al, 2011).…”
Section: Architecture Of Rssupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with the previous studies (Diener et al, 1993;Patel-King et al, 2004;Sivadas et al, 2012), RSP3 appears to be localized all the way from the RS head to the root of the RS stalk, and one spoke contains at least two copies of RSP3 (Figs. 2 and S1; Wirschell et al, 2008;Diener et al, 2011).…”
Section: Architecture Of Rssupporting
confidence: 80%
“…2), a distribution that is unique among RSPs and is consistent with the previous deletion mutant analysis of RSP3 (Sivadas et al, 2012). RSP11 has sequence similarity to the regulatory subunit (RIIa) of cAMP-dependent protein kinase (PKA), and it has been proposed to regulate flagellar beating through interaction with RSP3 .…”
Section: Architecture Of Rssupporting
confidence: 65%
“…RII overlay and deletion mutation analysis have demonstrated that RSP3 is an A-kinase anchoring protein (AKAP) located near the inner dynein arm (Gaillard et al 2001(Gaillard et al , 2006. AKAPs are a well-characterized class of scaffolding proteins that bind to PKA holoenzyme to define its locations within the cell (Sivadas et al 2012;Taylor et al 2004). RSP3 acts as an AKAP to control dynein activity by regulating axonemal PKA, a ubiquitous protein composed of two catalytic subunits and two regulatory subunits, which is involved in numerous regulatory events in the cell.…”
Section: Introductionmentioning
confidence: 98%
“…AKAP is a well-characterized class of scaffolding proteins that bind to PKA holoenzyme at defined locations within the cells (Sivadas et al 2012;Taylor et al 2004). These findings imply the crucial role of RSP3 in cilia and flagella motility and signaling transduction.…”
Section: Introductionmentioning
confidence: 95%
“…Keywords RSP3 · Nucleocytoplasmic shuttling · In utero electroporation · Neurogenesis · Cilia dynein activity by regulating axonemal cAMP-dependent protein kinase (PKA) (Gaillard et al 2001(Gaillard et al , 2006Sivadas et al 2012). AKAP is a well-characterized class of scaffolding proteins that bind to PKA holoenzyme at defined locations within the cells (Sivadas et al 2012;Taylor et al 2004).…”
Section: Introductionmentioning
confidence: 99%